Carbamates: A study on genotoxic, cytotoxic, and apoptotic effects induced in Chinese hamster ovary (CHO-K1) cells. Issue 5 (August 2015) - Soloneski, Sonia; Kujawski, Maciej; Scuto, Anna; Larramendy, Marcelo L.
Highlights Pirimicarb and zineb as well as its formulations were evaluated on CHO-K1 cells. The compounds were evaluated by genotoxicity and cytotoxicity endpoints. All compounds induced a significant and equivalent increase in MN frequencies. Carbamates triggered apoptosis when CHO-K1 cells were exposed for 24 h.